Formation of the Economic Security System of Tourism and Hospitality Enterprises - KRUPSKYI, Oleksandr P.; SARDAK, Sergii E.; KOLBUSHKIN, Yuriy P.; STASYUK, Yuliia M. (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The purpose of the paper is to consider genesis and approaches to forming a security culture of tourism and hospitality enterprises that are superstructures of economic, industrial, professional, household, ecological, psychological and social security. In the research, apart from general scientific methods, we used the collection and analysis of primary information obtained from the survey of 220 respondents. Three areas that have a decisive influence on the security of tourism and hospitality enterprises have been identified: organizational culture, decision-making responsibility, and competitiveness. The decision-making methods for different leadership styles were identified. There were conceptualized connection and strength of correlation between types of strategic decisions, leadership styles and organizational culture of tourism and hospitality enterprises. It has been proposed the factors’ configuration relevant to the security of tourism and hospitality enterprises, which focuses on the economic security formation as a function of organizational culture, responsibility for decision making and competitiveness. The styles of leadership and decision-making styles have been revealed, which determine the effectiveness of economic security of tourism and hospitality enterprises.